THE SETTLEMENT OF DISPUTES REGARDING DIVISION OF JOINT PROPERTY AFTER A DIVORCE IN THE CENTRAL ACEH REGENCY - Hazar Kusmayanti; Efa Laela fakhriah; Bambang Daru Nugroho (Universitas Islam Negeri Ar-Raniry, 2021)
This resarch reviews disputes revolving around the division of joint property after a divorce in the Central Aceh Regency using the methods; discussion with family, discussion by involving the customary institution Sarak Opat, and filing a claim to the Takengon Syar’iyah Tribunal. In general, division of joint property in the Central Aceh Regency is done by discussion through the customary institution Sarak Opat. The division of joint property after a divorce in the Central Aceh Regency that is done through discussion takes into account which household the child grew up in and how much money that household makes. Although this is not in accordance with the provisions of Indonesia’s Marriage Law and the Islamic Law Compilation, it may be in accordance with Article 37 of Indonesia’s Marriage Law and that this would not violate the rules within Islamic Law nor Customary Law, since in its core within Islamic Law and Customary Law there are specific rules regarding percentage of division of joint property following a divorce